Adoption the basis of spatial analysis and geographic information systems (GIS) techniques to development oil industry projects - Naji, Fanir Farooq O. (Journal of Petroleum Research and Studies, 2014)
It is recognized today that human lives the information age, which is characterized by the multiplicity of its data and the complexity of its aspects and the most important thing is characterized by "information" that will determine the progress of the people, the more able countries to devise ways to protect the information and how to make the best use of them whenever it is an indication of its progress and its ability to face obstacles to development and the information sources are diverse and interrelated up to the level of complexity that they can be analyzed and dealt with the existence of developed computer systems, that stored and processed the information .And because maps are also considered sources of information which use in management and project planning, and being an important means of connecting ideas and planning them so it necessitated the need for the emergence of advanced systems have the ability to draw and design schemes and production of digital maps. With possibility of linking information (metadata) with the real location on the Earth’s surface, called the (spatial data). The emergence of these systems are scientific leap on the in geographic science especially spatial data that has accumulated over the centuries and resulted in a huge amount of data and information. These systems added a lot in the field of building spatial database which can updating and help in treating maps accurately and effectively combines the advantages of the two systems (information systems and systems of digital maps), which was named "GIS" systems which electronic NO.10 digital competent to enter, store and retrieve, analyze data . And connect them with large areas of maps that can not be saved on security on the paper. The data is saved with maps in a coherent manner so as to facilitate the user to display the data with maps and several methods as well as a calculation processing to extract the results and reports in a few time and effort and use them in decision-making which helps to speed the study and analysis the information and support decision-makers in a number of important decisions concerning projects which requires accuracy and speed.